If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Cos(6x) + 3cos(3x) = 1 Remove parenthesis around (6x) osC * 6x + 3cos(3x) = 1 Reorder the terms for easier multiplication: 6osC * x + 3cos(3x) = 1 Multiply osC * x 6osxC + 3cos(3x) = 1 Remove parenthesis around (3x) 6osxC + 3cos * 3x = 1 Reorder the terms for easier multiplication: 6osxC + 3 * 3cos * x = 1 Multiply 3 * 3 6osxC + 9cos * x = 1 Multiply cos * x 6osxC + 9cosx = 1 Reorder the terms: 9cosx + 6osxC = 1 Solving 9cosx + 6osxC = 1 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6osxC' to each side of the equation. 9cosx + 6osxC + -6osxC = 1 + -6osxC Combine like terms: 6osxC + -6osxC = 0 9cosx + 0 = 1 + -6osxC 9cosx = 1 + -6osxC Divide each side by '9osx'. c = 0.1111111111o-1s-1x-1 + -0.6666666667C Simplifying c = 0.1111111111o-1s-1x-1 + -0.6666666667C Reorder the terms: c = -0.6666666667C + 0.1111111111o-1s-1x-1
| 8-1/6x^2-1/3x=0 | | -7/8s=-6/7 | | 2*ln(2)-2=x | | 5x-15=2x+15 | | y=8+4x-x^2 | | 2(1/2)x | | 1+y=2.5X | | kx^2+4x+k-3=0 | | 14/45=14/x | | 23x+15=38 | | 100+56=h+75 | | 23x-15=38 | | 3(y-4)-3(y-9)=5(y+4) | | -7-5x=3 | | 16h=79h | | f(x)=-7x+10 | | 3x+1y=323.7 | | X^2+6X-2= | | 2.9x+4-8.9x=10 | | 5c-2d=36 | | 2logx-log(x-3)=1 | | 1/2x-1/3=2/x | | 0.2x=-3.3 | | 20+34=27+1 | | (4y+5)(3y^2-2y-4)= | | (4y+5)(3y^2-2y-4)=equation | | 4x-3(2x)-4=0 | | (2x+15)+(3x-20)+(x+15)=360 | | X(x+4)(x-3)=0 | | 10=4A-3 | | x-3=2+x | | 3x+5y+8=0 |